2023
DOI: 10.1108/jedt-06-2022-0299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risks affecting international construction joint venture (ICJV) projects in Ghana

Abstract: Purpose The failure rate of international construction joint venture (ICJV) projects has been noted to be high in developing countries due to the complexity and risky nature of construction projects in the international market. The purpose of this study is to identify and evaluate the risks facing ICJV projects in Ghana. Design/methodology/approach A risk register was developed through a comprehensive literature review. The identified risks were then used in a questionnaire survey involving local and foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In Ghana, there is an increasing concern among construction stakeholders because of factors, including inflation, influencing construction projects from the start to completion (Famiyeh et al, 2017;Damoah et al, 2020;Ansah et al, 2021;Akunyumu et al, 2023). Similarly, Kaliba et al (2009) identified inflation as one of the root causes of cost and time overruns in Zambia Road construction projects.…”
Section: Literature Review 21 Overview Of the Impact Of Inflation On ...mentioning
confidence: 99%
“…In Ghana, there is an increasing concern among construction stakeholders because of factors, including inflation, influencing construction projects from the start to completion (Famiyeh et al, 2017;Damoah et al, 2020;Ansah et al, 2021;Akunyumu et al, 2023). Similarly, Kaliba et al (2009) identified inflation as one of the root causes of cost and time overruns in Zambia Road construction projects.…”
Section: Literature Review 21 Overview Of the Impact Of Inflation On ...mentioning
confidence: 99%
“…Although previous studies have been conducted to manually evaluate investment risk in international construction projects 4 , 5 , in most cases, the results and solutions are limited to risk assessment management 6 , 7 . For example, Akunyumu 8 has used questionnaire survey to recognized ten critical risk variables, which hold the ideal that unstable currency exchange rates, inflation, design changes, high-interest rate, budget overrun are important for managers. Face many risk information, some researchers regard that the framework of tacit knowledge externalization in international construction projects are key tools to manage risk 9 .…”
Section: Introductionmentioning
confidence: 99%